Prevalence of type 2 diabetes and impaired fasting glucose: cross-sectional study of multiethnic adult population at the United States-Mexico border Prevalencia de diabetes tipo 2 y de alteración de la glucosa en ayunas: estudio transversal de una población adulta multiétnica en la frontera México-Estados Unidos - Beatriz A. Díaz-Apodaca; Shah Ebrahim; Valerie McCormack; Federico G. de Cosío; Rosalba Ruiz-Holguín (Pan American Health Organization, 2010)
OBJETIVE: To estimate prevalence of type 2 diabetes (diabetes) and impaired fasting glucose (IFG) in the border region between the United States of America and Mexico, by ethnic origin and country of residence; identify risk factors associated with both conditions; and explore the extent to which these factors account for cross-border or ethnic disparities in prevalence. METHODS: From April 2001 to November 2002, Phase I of the U.S.-Mexico Border Diabetes Prevention and Control Project, a prevalence study of diabetes and its risk factors, was conducted at the U.S.-Mexico border using multistage cluster sampling. A questionnaire was administered on diabetes (self-reported) and lifestyle and a physical examination and blood sample were obtained. A total of 4 027 adults participated in the study: 2 120 Hispanics from the Mexican side of the border and 1 437 Hispanics and 470 non-Hispanics (of whom 385 were classified as "white") from the U.S. side of the border. RESULTS: The age-adjusted prevalence of self-reported and unrecognized diabetes in Hispanics was 15.4% (16.6% on the Mexican side of the border and 14.7% on the U.S. side). The age-adjusted prevalence of IFG was similar on both sides of the border (14.1% on the Mexican side and 13.6% on the U.S. side). CONCLUSIONS: Established risk factors for diabetes (e.g., age, obesity, and family history) were relevant and there was an inverse relationship between diabetes and education and socioeconomic level. While diabetes prevalence is high on both sides of the U.S.-Mexico border, one-fourth of the cases remain undiagnosed, suggesting a need for development and implementation of a public health program for prevention, diagnosis, and control of diabetes in the region. OBJETIVO: Calcular la prevalencia de la diabetes de tipo 2 (diabetes) y de la alteración de la glucosa en ayunas en la zona fronteriza entre México y los Estados Unidos, por origen étnico y país de residencia; identificar los factores de riesgo asociados a ambas afecciones, y explorar en qué grado estos ...